A comparative study of single incision laparoscopic cholecystectomy versus four port laparoscopic cholecystectomy - Raina, Saurabh; Gulshan, Javaid Iqbal; Bhasin, Sanjay Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Since Langenbuch's pioneering open cholecystectomy in 1882, surgical approaches to gall bladder diseases have seen continual evolution. Laparoscopic surgery has emerged as the preferred method for treating benign gall bladder conditions, offering benefits like decreased postoperative discomfort and enhanced cosmetic outcomes. Variations to the traditional four-port laparoscopic cholecystectomy have been developed to further refine the procedure. Methods: A comparative randomized study was carried out at the Department of Surgery, Govt. Medical College and Hospital Jammu, spanning from November 1, 2018, to October 31, 2019. Thirty eligible patients were recruited, with 15 assigned to undergo single-incision laparoscopic cholecystectomy (SILC - Group A) and 15 assigned to undergo four-port laparoscopic cholecystectomy (Group B). Results: The study comprised patients aged between 20 and 60 years, with mean ages of 41.9 years for Group A and 40.3 years for Group B. Substantial variances were noted between the two groups concerning surgery duration, conversion rates, postoperative pain scores, and hospital stay. Conclusions: Based on our findings, single-incision laparoscopic cholecystectomy (SILC) cannot be deemed a standard operative procedure, mainly due to its cost implications and the necessity for specialized instruments. At present, SILC does not serve as a substitute for four-port laparoscopic cholecystectomy. Continued research and advancements are warranted to solidify SILC as a feasible alternative.